2011
DOI: 10.1029/2011ja016715
|View full text |Cite
|
Sign up to set email alerts
|

Latitude and local time variations of topside magnetic field-aligned ion drifts at solar minimum

Abstract: The movement of ions along terrestrial magnetic field lines frequently causes the redistribution of ionization between northern and southern hemispheres. This behavior is known as interhemispheric transport and is an important source of coupling between the ion and neutral gases in the upper atmosphere. The Communications/Navigation Outage Forecast System (C/NOFS) satellite and the Coupled Ion Neutral Dynamics Investigation (CINDI) provide an opportunity to directly measure ion velocities and ion densities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…The ranges of these orbital swaths were chosen to encompass the usable ion flow data from CINDI during this time period. During the extended solar minimum starting in 2008 only the cross track ion flow data below 550 km were usable because the percentage of O+ above that altitude was too small for the ion drift meter to function accurately Burrell et al, 2011). But by September 2011, the increased solar activity had increased the percentage of O+ at all altitudes so that the quality of the cross track ion flow data were good up to 750 km.…”
Section: Analytical Approachmentioning
confidence: 96%
“…The ranges of these orbital swaths were chosen to encompass the usable ion flow data from CINDI during this time period. During the extended solar minimum starting in 2008 only the cross track ion flow data below 550 km were usable because the percentage of O+ above that altitude was too small for the ion drift meter to function accurately Burrell et al, 2011). But by September 2011, the increased solar activity had increased the percentage of O+ at all altitudes so that the quality of the cross track ion flow data were good up to 750 km.…”
Section: Analytical Approachmentioning
confidence: 96%
“…The longitude regions separate the observations into regions of common magnetic declination and offset between geomagnetic and geographic equators while the local time regions consider morning, day, dusk and nighttimes. The longitude divisions are the same as those used by West et al [1997] and are shown in Table 1 along with the seasonal and local time divisions, which were previously used by Burrell et al [2011]. When considering the explicit dependence of the field‐aligned drift on longitude or local time the corrected magnetic latitude is constrained to ±5°.…”
Section: Datamentioning
confidence: 99%
“…These cadences were determined by the sample rate. Further data processing details may be found in the work of Burrell et al [2011].…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations